2019
DOI: 10.1002/chem.201902434
|View full text |Cite
|
Sign up to set email alerts
|

Covalent versus Noncovalent Binding of Ruthenium η6p‐Cymene Complexes to Zinc‐Finger Protein NCp7

Abstract: Ruthenium-arene complexesa re au nique class of organometallic compounds that have been shown to have prominent therapeutic potencies.H ere, we have investigated the interactions of Ru-cymene complexes with az incfinger protein NCp7, aiming to understand the effects of various ligandso nt he reaction. Five different binding modes were observed on selected Ru-complexes. Ru-cymene complex can bind to proteins through either noncovalent binding aloneo rt hrough ac ombinationo fc ovalent and nonco-valentb inding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…It seems like it is a general trend that chlorido ligand is easier exchanged with water than the pta ligand, i.e., chlorido ligand is more labile than pta. This also affects the kinetics of interactions with biomolecules and thus, also their biological activity [43][44][45].…”
Section: Kinetics Of the Interaction Of Ru Complex (1) And (2) With Hmentioning
confidence: 99%
“…It seems like it is a general trend that chlorido ligand is easier exchanged with water than the pta ligand, i.e., chlorido ligand is more labile than pta. This also affects the kinetics of interactions with biomolecules and thus, also their biological activity [43][44][45].…”
Section: Kinetics Of the Interaction Of Ru Complex (1) And (2) With Hmentioning
confidence: 99%
“…In our previous studies, we have found that the behavior of the complexes depends on the type of the ligand and together with all above mentioned factors affect the kinetics of interactions with biomolecules, and thus, also their biological activity [ 40 , 41 , 42 ]. Previously, we have already reported stability investigations of some organoruthenium(II)-pyrithionato complexes [ 22 , 24 , 32 ] as well as of structurally related organoruthenium(II) compounds [ 40 , 41 , 42 ] by NMR, MS, and UV-Vis spectroscopies. Firstly, we have shown by 1 H NMR that compound 1a is stable in DMSO-d 6 /D 2 O solvent system [ 22 ] and later also confirmed the stability of 1a complex in the D 2 O solution containing NaCl [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…These molecules can, however, also react with metallodrugs possessing labile ligands [39]. In our previous studies, we have found that the behavior of the complexes depends on the type of the ligand and together with all above mentioned factors affect the kinetics of interactions with biomolecules, and thus, also their biological activity [40][41][42]. Previously, we have already reported stability investigations of some organoruthenium(II)-pyrithionato complexes [22,24,32] as well as of structurally related organoruthenium(II) compounds [40][41][42] by NMR, MS, and UV-Vis spectroscopies.…”
Section: Stability Of Organoruthenium(ii) Pyrithione Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…2527 In recent years, we have been intensely investigating the biological properties and anticancer potential of metal complexes of hydroxyquinolines. 2834 For instance, we synthesized an organoruthenium complex (Figure 1; center bottom) of clioquinol ( cqH ) and showed that the complex ( Ru-cq ) exhibits selective toxicity toward leukemic cell lines through a caspase-dependent mechanism of cell death. 28 Moreover, we determined that the complex Ru-cq does not interact with DNA and shows proteasome-independent inhibition of the NFκB signaling pathway without affecting cell-cycle distribution.…”
Section: Introductionmentioning
confidence: 99%